Empowering the Physiotherapy Profession in Ethiopia through Leadership Development within the Doctoring Process - Footer, Cheryl Burditt; Tsegaye, Hailu Seifu; Yitnagashaw, Tesfaye Asnake; Mekonnen, Wintana; Shiferaw, Tizita Destaw; Abera, Endashaw; Davis, Alice (Frontiers in Public Health, 2017)
Ethiopia recently introduced the Doctor of Physiotherapy (DPT) degree at Addis Ababa University as a mechanism to increase the work force capacity of primary care providers in the health sector. The DPT program was supported by an international academic partnership and was designed to empower physiotherapists as leaders to move the profession forward. The curriculum was framed by core pedagogical principles and strategies and was phased into two programs. First, the 4-year Advanced Standing DPT program focused on developing registered Ethiopian physiotherapists with BSc degrees as academic faculty. Second, these new faculty would then sustain a 6-year Generic DPT program that would matriculate students upon graduation from high school. The curriculum represented depth and breadth of foundation and clinical sciences, evidence-based practice, clinical reasoning skills, and inter-professional education opportunities. A leadership thread provided opportunities to develop skills necessary to effectively navigate and manage the challenges faced by the profession. The main outcomes included (1) an eight-year international partnership, (2) the academic performance of students, and (3) and leadership capabilities as demonstrated through activities and assignments. While the program has been criticized as an unnecessary extravagance for Ethiopia, the advantages of the DPT degree were revealed in a direct comparison to other academic PT programs in Ethiopia. In the end, because the DPT is new to the country, it will take time to fully understand the true impact within the Ethiopian health system.